Penerapan Strategi Pemasaran Online untuk Meningkatkan Kinerja Bisnis di Kalembo Koffie, Kota Binjai, Sumatera Utara: Implementation of Online Marketing Strategies to Enhance Business Performance at Kalembo Koffie, Binjay City, North Sumatra - Refiswal, Refiswal; Arman, Iman; Astuti, Linda Tri Wira; Butarbutar, Yenny Laura KD (Journal of Integrated Agribusiness, 2024)
This study aims to develop an effective online marketing plan tailored to the internal and external conditions of Kalembo Koffie and to analyze its business performance based on sales figures and social media followers following the implementation of an online marketing strategy. A qualitative research method was employed. The study's results indicate that Kalembo Koffie has adopted digital marketing by focusing on social media marketing through content marketing. The types of core content created include promotional, entertainment, educational, and conversational themes. Marketing elements based on segmentation, target market, and positioning, as well as the marketing mix (7Ps), have been appropriately implemented. The preparation of an effective online marketing plan for Kalembo Koffie began with a SWOT analysis and progressed to scheduling marketing activities through a Content Calendar on its social media accounts. Kalembo Koffie's business performance, reflected by the increased follower count and regular content posting, shows improvement; however, it has not yet reached the target of 1,000 followers. Additionally, Kalembo Koffie experienced a 4.7% increase in transactions and a 21.19% rise in revenue.